TEKNIK STERILISASI DAN EFEKTIVITAS 2,4-D TERHADAP PEMBENTUKAN KALUS EKSPLAN DAUN NILAM (Pogostemon cablin Benth) IN VITRO - Fitriani, Yuyun; Wijana, Gede; Darmawati, Ida Ayu Putri (Journal of Agricultural Science and Biotechnology; Vol 8 No 1 (2019), 2019)
Patchouli plant (Pogostemon cablin Benth) is a plant that produce essential oil which is called patchouli oil. Indonesia is the largest supplier of patchouli oil in the world market, which contribute about 90%. Advantage of patchouli oil in the perfume industry is a fixative property, it has the ability to bind with other oils therefore the scent can last for long time and has yet to be made synthetically. However, it takes very long time to produce essential oils in the conventional production system, becouse the growth of patchouli plant is relative slow. One alternative to produce the raw material or patchouli plant faster is through the tissue culture. The sterilization technique and the growth regulator are main factor in tissue culture. Therefore the purpose of this study was to find a sterilization technique, as wel as the concentration of growth regulators 2,4-D (2,4diclorophenoxy acetic acid) in MS + coconut water medium. Sterilization with HgCl2  mercury chloride) at concentration 0.1% for 10 min was the best method of sterilization to minimize contamination. Plant growth regulators 2,4-D at concentration 0.5 ppm was found very affectivein accelerating the formation of patchouli leaf callus in vitro. The callus formation occured retatively fast (9.67 days) with cream-colour, crumb texture, and with diameter 1.21 cm. The fresh and dry weight of callus were 1.35 g and 0.76 g respectively.